If, then : a novel - Day, Kate Hope (Random House, 2019)
n the quiet haven of Clearing, Oregon, four neighbors find their lives upended when they begin to see themselves in parallel realities. Ginny, a devoted surgeon whose work often takes precedence over her family, has a baffling vision of a beautiful co-worker in Ginny<U+2019>s own bed and begins to doubt the solidity of her marriage. Ginny<U+2019>s husband, Mark, a wildlife scientist, sees a vision that suggests impending devastation and grows increasingly paranoid, threatening the safety of his wife and son. Samara, a young woman desperately mourning the recent death of her mother and questioning why her father seems to be coping with such ease, witnesses an apparition of her mother healthy and vibrant and wonders about the secrets her parents may have kept from her. Cass, a brilliant scholar struggling with the demands of new motherhood, catches a glimpse of herself pregnant again, just as she<U+2019>s on the brink of returning to the project that could define her career. At first the visions are relatively benign, but they grow increasingly disturbing<U+2014>and, in some cases, frightening. When a natural disaster threatens Clearing, it becomes obvious that the visions were not what they first seemed and that the town will never be the same.